ANALISIS PERBANDINGAN METODE ECONOMIC ORDER QUANTITY (EOQ) DAN PERIODIC ORDER QUANTITY (POQ) DALAM PENGENDALIAN PERSEDIAAN BAHAN CUTTING DISK DAN CARBON GOUGING DI PT. STP - Annisa Purbasari; Hery Irwan; Wulandari Apostolic (Universitas Riau Kepulauan, 2022)
Material inventory is one of the important elements to simplify the production process in the company. PT. STP is a company that produces module structures. This company often uses consumable materials, namely Cutting Disk and Carbon Gouging to work on its orders. The company controls the inventory of both materials using the FIFO (First in First out) method. However, the inventory costs incurred by the company with this method are still quite large and cause excess material stocks. This study aims to analyze the comparison of EOQ (Economic Order Quantity) and POQ (Periodic Order Quantity) methods in controlling the inventory of Cutting Disk and Carbon Gouging materials in PT. STP. The results showed that with the EOQ method, the ordering frequency became 13 times a year with a quantity per order of 1434 boxes for Cutting Disk material and the ordering frequency was 8 times a year with a quantity per order of 656 boxes for Carbon Gouging material. Meanwhile, the results of the POQ method obtained that the order frequency to be 12 times a year with a quantity per order of 1,498 boxes for Cutting Disk materials and the ordering frequency to be 6 times a year with a quantity per order of 852 boxes for Carbon Gouging materials. The results of the EOQ method obtained the total inventory cost of Cutting Disk materials of Rp. 929,455,735, - and Carbon Gouging of Rp. 1,828,712,584, - with the total inventory cost (TC) of the two materials of Rp. 2,758,168,319,-. While the results of the POQ method obtained the total inventory cost of Cutting Disk materials of Rp. 929,294,252,- and Carbon Gouging of Rp. 1,828,902,262,- with the total inventory cost (TC) of the two materials of Rp. 2,758,196,514,-.